Large Cell Carcinoma Mimicking Non Resolving Pneumonia (Journal of Medicine, 2011)
Fever, chest pain, cough in a young lady usually does not ring any alarm bell. We present here a case of a young lady who had typical symptoms of community acquired pneumonia who initially responded to regular antibiotics but later was investigated to have large cell carcinoma. Presentation of lung cancer as non-resolving pneumonia is not a very common phenomenon and diagnosis can present a diagnostic challenge to the clinician. Keyword: Non-resolving pneumonia, Young lady, Chest pain, fever, Large cell Carcinoma, Bangladesh. DOI: http://dx.doi.org/10.3329/jom.v12i2.8423 JOM 2011; 12(2): 166-169